UJI EMPIRIS MODEL ASSET PRICING LIMA FAKTOR FAMA-FRENCH DI INDONESIA - Bambang Sutrisno; Irwan Adi Ekaputra (Jurnal Keuangan dan Perbankan, 2016)
The main purpose of this study is to evaluate and compare the performances of the Fama-French three- (FF3) and five-factor (FF5) models in the Indonesia stock market. This study also examines whether book-to-market factor (HML) is redundant in explaining the portfolio excess returns in Indonesia. This study employs asset pricing factor of the 2 x 3 sorts and excess returns of 25 Size-B/M, 25 Size-OP, dan 25 Size-Inv portfolios as dependent variables. This study employs Ordinary Least Square (OLS) with monthly time-series data from 2000 to 2015. Based on the average adjusted R2 from the two models, FF5 explains portfolio excess return variations better than FF3, although the profitability and investment factors only display weak effect on the excess returns. If we refer to Mertons (1973) zero-intercept criterion, the both models are not valid in Indonesia, because most intercepts are significant in each set of 25 portfolios. We also find that book-to-market factor is redundant in describing the variation of returns in Indonesia. The test of intercept difference between Indonesia and The US indicates that there are differences of abnormal return and market efficiency in both countries.